2021
DOI: 10.2147/prbm.s315068
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prosocial Cartoon Examples on Children’s Donating Behavior

Abstract: Purpose In this study, we examined whether prosocial cartoons could inspire children to donate toys to others immediately upon exposure. Participants and Methods Cartoons were rated as prosocial or control via 80 adults. One hundred and fifty-six children participated in the study ( M age = 5.29, SD = 0.79). Children in the experimental group were exposed to cartoons in which the main character had a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…However, they rejected bad moral values portrayed by the antagonists, such as stupidity, laziness, aggression, bullying, irascibility, dominance, boasting, lying, and pride. These findings are in line with studies by Astuti et al (2019) and Zhang et al (2021), who argued that narratives and character arcs in cartoons with positive moral values can influence children's ethical and moral choices in their daily lives. Moreover, preschool children go through an imitation process in their cognitive development, causing them to easily imitate what they see and hear (Hasanah & Much, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…However, they rejected bad moral values portrayed by the antagonists, such as stupidity, laziness, aggression, bullying, irascibility, dominance, boasting, lying, and pride. These findings are in line with studies by Astuti et al (2019) and Zhang et al (2021), who argued that narratives and character arcs in cartoons with positive moral values can influence children's ethical and moral choices in their daily lives. Moreover, preschool children go through an imitation process in their cognitive development, causing them to easily imitate what they see and hear (Hasanah & Much, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…and prosocial behaviours may be related to media contents, prosocial games being more likely played by girls. 56,57 Our findings suggest no evidence that lifestyle patterns at age 5 are associated with BMI z-scores at age 8, consistent with some previous cross-sectional studies. 10 Seghers et al suggested that physiological demands of growth and maturation may mask the relation between unhealthy lifestyle patterns and BMI.…”
Section: Discussionsupporting
confidence: 88%
“…This may thus partially explain why associations between a healthy lifestyle pattern and symptoms of hyperactivity‐inattention as well as prosocial behaviours were observed in boys and not as clearly in girls. It can be assumed that the girl‐specific association between the mixed lifestyle pattern (commonly characterised in boys and girls by high screen and physical activity times) and prosocial behaviours may be related to media contents, prosocial games being more likely played by girls 56,57 …”
Section: Discussionmentioning
confidence: 99%
“…Their behavior will return to a basic level when a neutral toy is given. Another study also revealed that children's prosocial behavior increased after they watched together a television program designed specifically for learning (Mares & Woodard, 2005;Zhang et al, 2021;Zieunska & Chambers, 1995). The television program was reported to be effective in encouraging children's prosocial behavior during free play, encouraging cooperative attitudes, and preventing antisocial behavior.…”
Section: Introductionmentioning
confidence: 97%